MTHFR rs1801133 Polymorphism Is Associated With Liver Fibrosis Progression in Chronic Hepatitis C: A Retrospective Study - Pineda-Tenor, Daniel; Gómez-Moreno, Ana Zaida; Sánchez-Ruano, Juan José; Artaza-Varasa, Tomas; Virseda-Berdices, Ana; Fernández-Rodríguez, Amanda; Mendoza, Pedro Molina; Jiménez-Sousa, María Ángeles; Resino, Salvador (Frontiers in Medicine, 2020)
Background: The MTHFR (methylenetetrahydrofolate reductase) rs1801133 polymorphism leads to higher circulating levels of homocysteine, which is related to several liver diseases. We aimed to evaluate the relationship between MTHFR rs1801133 polymorphism and liver fibrosis progression in HCV-infected patients. Methods: We conducted a preliminary retrospective cohort study in 208 non-cirrhotic HCV-infected patients. These subjects had at least two liver stiffness measurements (LSM), which were assessed using transient elastography, and no patient had cirrhosis at baseline. We analyzed the association between MTHFR rs1801133 and outcome variables using Generalized Linear Models. Results: HCV-infected patients were 47 years old, around 54% were males, a low frequency of high alcohol intake (13.5%) or prior use of intravenous drugs (10.1%). A total of 26 patients developed cirrhosis (LSM1 ≥12.5) during a median follow-up of 46.6 months. The presence of the rs1801133 C allele showed an inverse association with the LSM2/LSM1 ratio (adjusted AMR = 0.90; 95%CI = 0.83 - 0.98; p = 0.020) and the cirrhosis progression (adjusted OR= 0.43; 95%CI= 0.19 - 0.95; p= 0.038). Besides, rs1801133 CT/CC genotype had an inverse association with the LSM2/LSM1 ratio (adjusted AMR= 0.80; 95%CI =0.68 - 0.95; p= 0.009) and the cirrhosis progression (adjusted OR= 0.21; 95%CI= 0.06 - 0.74; p= 0.015). Conclusions: MTHFR rs1801133 C allele carriers presented a diminished risk of liver fibrosis progression and development of cirrhosis than rs1801133 T allele carriers. This statement supports the hypothesis that MTHFR rs1801133 polymorphism appears to play a crucial role in chronic hepatitis C immunopathogenesis.